Presupposition on The Main Characters of Frozen Movie Script - Maratu Solehah; Anita Anita; Tatu Siti Rohbiah (Wanastra: Jurnal Bahasa dan Sastra, 2022)
This study was conducted to investigate kind and the meaning of presupposition that occur in Frozen Movie Script by using pragmatics approach. The objectives of this study are 1) To find the types of the presupposition that used in the main characters in frozen movie script. 2) To describe the interpretation meaning of the presuppositions that found in Frozen movie script. This study is qualitative research applying content analysis. The data analysis was conducted by watching the movie from beginning until the end. In this research, the writer used distributional method to select utterance in the movie script to classify the data into kinds of presupposition and writer also used distributional method to analyze the data. The findings of this research are 50 utterance were found, there are 15 existential presupposition, 4 factive presupposition, 2 non factive presupposition,9 lexical presupposition, 17 structural presupposition, and 3 counterfactual presupposition. To know the interpretation meaning of presupposition the writer watching the movie from the beginning until the end of the movie, she read and analyze the script of the movie, then she relates to the situation and context that occurs in the storyline. Therefor she concluded that every presupposition produce it has meaning that want to send by speaker to listener, every presupposition it can depends on the condition or the situation when the speaker said the utterance.